Transformasi Profesi Akuntan di Era Artificial Intelligence (AI) : Systematic Literature Review - Bon, Sergius Fribontius; Arthana , I Komang (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This research aims to determine the impact of Artificial Intelligence (AI) on the accounting profession. This research uses the Systematic Literature Review (SLR) method to systematically evaluate previous research in order to increase the depth of analysis. Based on the results of the analysis, there were 12 articles that met the criteria. Based on the results of research using the Systematic Literature Review (SLR) method, the impact of the presence of AI on the accounting profession is, firstly, an increase in accuracy. Second, it can detect fraud. Third, increased efficiency, with AI the accounting process can be carried out more quickly and efficiently. Meanwhile, the challenges in using AI are, firstly, there are no standards for the use of AI in accounting and the rules regarding the use of AI in finance are still unclear. Second, AI cannot yet replace humans in making ethical judgments in complex situations. Third, you need to have new skills in analyzing data, understanding programming, and using AI tools. Fourth, the use of AI requires high costs.